High EGFR protein expression and exon 9 PIK3CA mutations are independent prognostic factors in triple negative breast cancers. Issue 1 (December 2015) - Jacot, William; Mollevi, Caroline; Fina, Frédéric; Lopez-Crapez, Evelyne; Martin, Pierre-Marie; Colombo, Pierre-Emmanuel; Bibeau, Frédéric; Romieu, Gilles; Lamy, Pierre-Jean
Abstract Background Triple negative breast cancers (TNBC) are a more aggressive subset of breast cancer. A better understanding of its biology could allow the rational development of targeted therapies. Methods We extensively analyzed the EGFR/PI3K/PTEN axis in a large, homogeneous population of TNBC to help defining the putative role of anti-EGFR and -PI3K targeted therapies in this setting.EGFR gene amplification, EGFR protein expression, PIK3CA andPTEN gene alterations (two members of EGFR downstream pathways) and their clinicopathological and prognostic implications were analyzed in 204 TNBC samples from European patients. Results EGFR amplification was detected in 18 of the 204 TNBC specimens (8.9 %) and was significantly associated with higher EGFR protein levels. FourteenPIK3CA mutations were identified in exon 9 (6.7 %), and 17 in exon 20 (8.3 %).PIK3CA mutations, especially in exon 9, were significantly associated with grade I-II tumors.PTEN deletions were detected in 43 samples (21.50 %) and were significantly associated with grade III tumors (p  < 0.001). Univariate analysis showed a significant association between relapse-free survival (RFS), T and N stage and exon 9PIK3CA mutations. Overall survival was significantly associated with T stage, N stage and adjuvant chemotherapy, which was administered to 70.3 % of patients. In multivariate analyses, T stage, N stage, presence of exon 9PIK3CA mutations and high EGFR protein level were independent poor prognostic factors for RFS, while adjuvant chemotherapy was associated with a better outcome. Conclusions High EGFR protein expression and exon 9PIK3CA activating mutations are independent prognostic factors in TNBC. The efficacy of anti-PI3K targeted therapies needs to be evaluated in this setting.